Entrepreneuship Education And Employabiliy Among Babcock University Students - Uwannah, Ngozi Caroline; Uwannah, Anelechi Onyemeze; Ojelabi, Dolapo Ruth (Advances in Social Sciences Research Journal, 2018)
Several attempts have been made at encouraging entrepreneurial activities in Nigeria in the past but observation has shown that these efforts failed due to various constraints. Hence this study investigated the extent at which entrepreneurship education determines employability among Babcock University students. A descriptive survey research design was adopted in the study and a total sample of three hundred and thirty (330) undergraduates of Babcock University in their final year were drawn through stratified random sampling technique as subject of study. Self-developed instruments namely Students’ Assessment of Entrepreneurship Education Questionnaire; consisting of 13 items with a reliability co-efficient of 0.68, and Employability Questionnaire with 6 items was used to test the influence of entrepreneurship education on employability with a reliability co-efficient of 0. 73. The study adopted linear regression analysis to test the hypothesis while mean and standard deviation were employed to analyse the research questions at 0.05 level of significance. The findings revealed that entrepreneurship education is a significant determinant of employability among Babcock University undergraduates. Further analysis revealed that entrepreneurship education is beneficial and have positive impact on them. It was recommended among other things that skill acquisition programmes should be incorporated into the school’s curriculum as a course to be taken by all students regardless of their level and course of study.